Use of Online Dispute Resolution in Realizing Restorative Justice in E-Commerce Disputes - Nanda Dwi Rizkia; Hasriyanti; Putri Ayi Winarsasi; Lina Maulidiana; Wahab Aznul Hidaya (Warmadewa Press, 2024)
This research aims to explore the potential for using Online Dispute Resolution as a tool in realizing restorative justice in e-commerce disputes. Through normative juridical research methods, with a statutory approach, this research analyzes secondary data in the form of primary, secondary and tertiary legal materials. The research results show that Online Dispute Resolution can be an effective tool in resolving e-commerce disputes quickly, cheaply and effectively without hampering the parties' business activities. The use of Online Dispute Resolution supports the principles of restorative justice by facilitating broader participation, effective communication, relationship maintenance, process efficiency, and empowerment of all parties involved, helping to create a space conducive to dialogue, understanding, and healing of relationships.